A multicomponent exercise intervention to improve physical functioning, cognition and psychosocial well-being in elderly nursing home residents: A study protocol of a randomized controlled trial in the PROCARE (prevention and occupational health in long-term care) project - Cordes, Thomas; Bischoff, Laura L.; Schöne, Daniel; Schott, Nadja; Voelcker-Rehage, Claudia; Meixner, Charlotte; Appelles, Luisa-Marie; Bebenek, Michael; Berwinkel, Andre; Hildebrand, Claudia; Joellenbeck, Thomas; Johnen, Bettina; et al. (BMC Geriatrics, 2019)
Background: Older adults, who are living in nursing homes that provide a high level of long-term nursing care, are characterized by multimorbidity and a high prevalence of dependency in activities of daily living. Results of recent studies indicate positive effects of structured exercise programs during long-term care for physical functioning, cognition, and psychosocial well-being. However, for frail elderly the evidence remains inconsistent. There are no evidence-based guidelines for exercises for nursing home residents that consider their individual deficits and capacities. Therefore, high-quality studies are required to examine the efficacy of exercise interventions for this multimorbid target group. The purpose of this study is to determine the feasibility and efficacy of a multicomponent exercise intervention for nursing home residents that aims to improve physical and cognitive functioning as well as quality of life. Methods: A two-arm single-blinded multicenter randomized controlled trial will be conducted, including 48 nursing homes in eight regions of Germany with an estimated sample size of 1120 individuals. Participants will be randomly assigned to either a training or a waiting time control group. For a period of 16 weeks the training group will meet twice a week for group-based sessions (45-60 min each), which will contain exercises to improve physical functioning (strength, endurance, balance, flexibility) and cognitive-motor skills (dual-task). The intervention is organized as a progressive challenge which is successively adapted to the residents' capacities. Physical functioning, cognitive performance, and quality of life will be assessed in both study groups at baseline (pre-test), after 16-weeks (post-treatment), and after 32-weeks (retention test, intervention group only). Discussion: This study will provide information about the efficacy of a multicomponent exercise program in nursing homes (performance, recruitment). Results from this trial will contribute to the evidence of multicomponent exercises, which specifically focus on cognitive-motor approaches in the maintenance of mental and physical functioning. In addition, it will help to encourage older adults to actively engage in social life. Furthermore, the findings will lead to recommendations for health promotion interventions for frail nursing home residents. Trial registration: The trial was prospectively registered at DRKS.de with the registration number DRKS00014957 on October 9, 2018.
CRIS-Team Scopus Importer:2020-02-21
Keywords: ADL; Aged; Clinical trial; Cognition; Exercise; Frailty; Intervention; Nursing home; Physical activity; Physical function